KAJIAN INDEKS KEPUASAN MASYARAKAT LAYANAN KEUANGAN DI KABUPATEN SERANG, PROVINSI BANTEN - Ernawati Ernawati; Agus Lukman Hakim; Hanifah Hanifah; Siti Yuniar (Jurnal Bina Bangsa Ekonomika, 2024)
The Serang Regency Government, specifically the Serang Regency BPKAD, has carried out the mandate of Law no. 25 of 2009 concerning Public Services and Government Regulation no. 96 of 2012 concerning Implementation of Law Number 25 of 2009 concerning Public Services, namely carrying out service satisfaction surveys. This activity aims to assess the level of satisfaction with the public services provided by BPKAD Serang Regency. The research approach used is descriptive quantitative. The data collection technique was by distributing questionnaires to service users from Serang district regional apparatus as many as 59 respondents who came from various regional apparatus in Serang Regency. The analysis technique uses bivariate and univariate analysis with reference to the Minister of State Civil Apparatus and Bureaucratic Reform Regulation No. 14 of 2017. The research results show that service users from regional apparatus in Serang Regency are satisfied with the services provided by BPKAD with a community satisfaction index score of 3.119, equivalent to 77.98, where the service quality is "B" and the performance of the service unit is good